Dairede analitik fonksiyonların sınır davranışı ve majorantlar - Akyel, Tuğba (Gebze Teknik Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2016)
Bu tezde, birim dairede holomorf, sınırlı fonksiyonların sınır davranışı incelenmiş olup, sınırda Schwarz Lemması'nın farklı versiyonları ele alınmıştır. Birim dairede holomorf olan fonksiyonların bir sınıfında, sınır noktasında açısal limitin mevcutluğu varsayılarak bu noktadaki açısal türevin modülünün aşağıdan değerlendirilmeleri elde edilmiştir. İncelenen fonksiyonların tek katlı ve çok katlı olması halleri ayrı ayrı ele alınmış olup, elde edilen kesin eşitsizliklerde fonksiyonun bir iç noktadaki değeri ve farklı mertebeden türevleri kullanılmıştır. Ayrıca Burns-Krantz-Chelst Teklik Teoremi'nin farklı bir versiyonu için daha genel sonuçlara ulaşılmıştır.

In this thesis, the boundary behaviour of the bounded holomorphic function in the unit disc has been examined and the different versions of boundary Schwarz Lemma have been discussed. In a class of holomorphic functions on the unit circle, assuming the existence of angular limit on the boundary point, the estimations below of the modulus of angular derivative have been obtained. Being univalent and multivalent of examined functions has been investigated separately and the value of the function in an inner point and its derivatives from different order have been used in obtained sharp inequalities. Also, for a different version of the uniqueness theorem of Burns-Krantz-Chelst, more general results have been reached.
The boundary behaviour of the analytic functions in the disc and majorants
Keywords: Matematik; Mathematics